Specificities involved in the initiation of retroviral plus-strand DNA. - Luo, G X (1990)
Reverse transcription of the retroviral RNA genome begins with tRNA-primed synthesis of a minus-strand DNA, which subsequently acts as the template for the synthesis of plus-strand DNA. This plus-strand DNA is initiated at a unique location and makes use of a purine-rich RNA oligonucleotide derived by RNase H action on the viral RNA. To determine the variables that are relevant to successful specific initiation of plus-strand DNA synthesis, we have used nucleic acid sequences from the genome of Rous sarcoma virus along with three different sources of RNase H: avian myeloblastosis virus DNA polymerase, murine leukemia virus DNA polymerase, and the RNase H of Escherichia coli. Our findings include evidence that specificity is controlled not only by the nucleic acid sequences but also by the RNase H. For example, while the avian reverse transcriptase efficiently and specifically initiates on the sequences of the avian retrovirus, the murine reverse transcriptase initiates specifically but at a location 4 bases upstream of the correct site.